Anthropometric and motor characteristics of South African national level female soccer players - Booysen, M. J.; Gradidge, P. J.-L.; Constantinou, D. (Journal of Human Kinetics, 2019)
Data regarding anthropometric and motor characteristics of elite national level female soccer players are scarce. Determining these characteristics may likely assist in evaluating the specificity of current training programmes, identify players who might lack specific qualities deemed critical for the successful execution of their tactical roles, and benchmark norms for developing future playing talent. Therefore, the aims of this study were to describe anthropometric and motor characteristics of South African national level female soccer players (n = 37) and determine possible differences with regard to their playing position. The following measurements and tests were performed: anthropometry (body mass index and sum-of-skinfolds), the countermovement jump, sprints (10 m, 20 m and 40 m), upper body muscle endurance (push-ups) and the Yo-Yo Intermittent Recovery Test - level 1. One-way analysis of variance revealed few differences in the main outcome variables. Fischer Least Significant Difference (LSD) showed that strikers had a greater body mass index than midfielders and defenders (both p = 0.04) and goalkeepers were heavier than defenders (p = 0.02). Goalkeepers were slower than strikers and defenders over 10 m (p = 0.01; p = 0.03) and 20 m (p = 0.001; p = 0.01). Midfielders were slower than strikers over 20 m (p = 0.02), and with strikers and defenders over 40 m (both p = 0.04). Defenders performed better than goalkeepers in the upper body muscle endurance test (p = 0.02). In conclusion, both strikers and defenders require speed to win ball possession, which may explain their fast sprint times. However, the similarity of certain motor characteristics across playing positions may suggest that conditioning coaches train players similarly, irrespective of their tactical position. The authors suggest that South African fitness professionals, particularly at a club level, develop physical conditioning programs specific to each field position. Furthermore, fitness assessments should occur on a continuous basis and comparisons should be made with existing normative data in order to guide the development of players over the course of their careers.